STRATEGI PENYIARAN RADIO REPUBLIK INDONESIA SURAKARTA UNTUK MENJANGKAU PERDESAAN MELALUI PROGRAM SIARAN PEDESAAN - Dhiva Pridayuliamita; Erwin Kartinawati; Sofia Ningsih Rahayu Putri (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2023)
Radio is a mass communication medium that has long been present among the people of Indonesia. Radio Republik Indonesia is a public broadcasting institution whose function is to provide information broadcast services, healthy entertainment education, and social control. The research entitled